Knowledge regarding obstetric danger signs among mother attending antenatal clinic at Scheer Memorial Adventist Hospital, Banepa, Kavre - Manandhar, Nirmala; Tamang, Manita (Nepal Medical College Journal, 2022)
Knowledge about obstetric danger signs is very crucial for preventing obsterric complication. Globally there was 211 maternal deaths per 1,00,000 live birth in 2017. The maternal mortality ratio for Nepal is 239 deaths per 1,00,000 live births in 2016. A descriptive cross sectional study was conducted to assess the knowledge regarding obstetric danger signs among pregnant mother attending ANC at Scheer Memorial Adventist Hospital, Banepa, Kavre, Nepal. Total 100 respondents were selected using non probability purposive sampling technique through a semi-structured interview questionnaire. Data were analyzed in SPSS-16 using descriptive statistics (mean, frequency, standard deviation and percentage) and inferential statistic Chi Square. The study shows that mean age of the respondents was 25.56±4.307. More than half of the respondents (53%) were from 15-25 age group. Majority of respondent (97%) were literate. Fifty six percent of respondents had adequate knowledge on obstetric danger signs, while 27% of respondents had moderate knowledge and few respondents (17%) had inadequate knowledge. There is no any significant relationship with knowledge with selected variable age, educational status, gravida, week of gestation and -number of ANC visit. Thus it is concluded about that the entire pregnant mother requires some interventions for the awareness regarding obstetric danger signs from the beginning of ANC visit. ANC visit should be focused more than eight times as recommended by WHO.